Complete mitochondrial genome sequence and mutations of the Glioma model inbred C57BL/6 mice strain. (3rd May 2016) - Gao, Hong-Zhi; Wang, Ming-Xi; Hu, Wei-Peng; Chen, Jun-Yan; Chen, Xiang-Rong; Lin, Ling
Abstract: In the present work we undertook the complete mitochondrial genome sequencing of an important glioma model inbred rat strain for the first time. The total length of the mitogenome was 16, 308 bp. It harbored 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and 1 non-coding control region (D-loop region). The mutation events were also reported.